The perception of encamped refugees on the value of education: The case of Zaatari camp - M. Nael, Sarah (AUC Knowledge Fountain, 2016)
In the light of the Syrian mass displacement, many children are finding refuge around the world. Taking Jordan as a host country to 655,365 Syrian refugees who reside in urban, rural areas or in camps. This thesis focuses on the educational aspect of Syrian refugee children in Zaatari refugee camp. A well-founded fear arises of having Syrian children become a lost generation amid the Syrian refugee crisis. Despite the establishment of nine schools in Zaatari camp, the enrolment rate is fifty percent of almost 30,000 school-aged children. This thesis aims at finding out the perception of parents on the value of education post refuge by asking three questions; 1. What are the perceptions of encamped parents in the Zaatari camp on education and its value to their children? 2. To what extent does parents' perception affect their children's participation in and attainment of education? 3. If parents’ perception on education is the factor affecting the low enrolment, what affects the parents’ perceptions? Can it be resolved? If perception is not a factor, what acts as a factor or factors leading to low enrolment in camps? The thesis aims at uncovering the reality of Zaatari camp from a refugee’s perspective, develop a better understanding of parents’ perception on camp education and encamped situations. It also aims at exploring refugee camp education in depth and analyzing refugees’ perception regarding education provisions. In attempt that the findings from this research fill the literature gap on refugee education in Zaatari camp and contribute to the field of research of refugee education. This research could act as an available resource for international organizations and stakeholders involved in refugee education and the findings could be taken into consideration in the future for decision makers and involved parties when setting up new camps and providing education services for refugees. The literature review tackles different themes related to refugee education, the importance of education for vulnerable children, children in emergencies and refugee children. It also discussed refugee education in camps and the provision of education services and its quality. The fieldwork of this study was conducted in Zaatari refugee camp in Jordan. It included interviewing sixteen families, four school directors and seven teachers and teacher assistants, in addition to UNICEF personnel. The findings of this study discussed education challenges in Zaatari camp, these challenges included resolved and unresolved challenges. It is concluded that behind the perceptions of parents on the value of education, the quality of education appears as a major issue that deserves more attention and efforts in the field of refugee studies. Parent's perception on the value of education was not affected by the post refuge conditions, except for a few parents. Despite the parents’ negative perceptions on the quality of education, parents still send their children to schools. This study is focusing on a crucial aspect of refugee education that scholars discussed regarding the quality of education being offered to refugees. The fact that Jordan and Syria share common aspects of language, culture and education system and syllabus, yet unresolved challenges remain. Are the same challenges that exist in Zaatari camp are faced outside the camp? Do these challenges extend beyond the Syrian refugee crisis? What is the situation and condition of refugees in other countries of the world? These are all questions emerged based on the finding s of this study, thus could be examined by further research.